Localization of Sound Sources in Normal Hearing and in Hearing Impaired People - NIEWIAROWICZ, Marek; KACZMAREK, Tomasz (Archives of Acoustics, 2011)
This article presents results of investigations of the angle of directional hearing acuity (ADHA) as a measure of the spatial hearing ability with a special emphasis on people with hearing impairments. A modified method proposed by Zakrzewski has been used – ADHA values have been determined for 8 azimuths in the horizontal plane at the height of the listeners’ head. The two-alternative-forced-choice method (2AFC), based on a new system of listeners’ responses (left – right instead of no difference – difference in location of sound sources) was the procedure used in the experiment. Investigations were carried out for two groups of subjects: normal hear- ing people (9 persons) and hearing impaired people (sensorineural hearing loss and tinnitus – 9 persons). In the experiment different acoustic signals were used: sinu- soidal signals (pure tones), 1/3 octave noise, amplitude modulated 1/3 octave noise, CCITT speech and traffic noises and signals corresponding to personal character of tinnitus for individual subjects. The results obtained in the investigations showed, in general, a better localization of the sound source for noise type signals than those for tonal signals. Inessential differences exist in ADHA values for particular signals between the two groups of subjects. On the other hand, significant differences for tinnitus signals and traffic noise signals were stated. A new system of listeners’ re- sponses was used and appeared efficient (less dispersion of results compared to the standard system).